2017
DOI: 10.1016/j.eururo.2017.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation Sequencing of Nonmuscle Invasive Bladder Cancer Reveals Potential Biomarkers and Rational Therapeutic Targets

Abstract: Background Molecular characterization of nonmuscle invasive bladder cancer (NMIBC) may provide a biologic rationale for treatment response and novel therapeutic strategies. Objective To identify genetic alterations with potential clinical implications in NMIBC. Design, setting, and participants Pretreatment index tumors and matched germline DNA from 105 patients with NMIBC on a prospective Institutional Review Board-approved protocol underwent targeted exon sequencing analysis in a Clinical Laboratory Impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
245
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(298 citation statements)
references
References 31 publications
33
245
2
4
Order By: Relevance
“…Previous studies have indicated that homozygous deletions of CDKN2A , a hallmark of advanced Uro tumors, correlate with progression and occur late in development . We did not observe this pattern, possibly due to difficulty to discriminate homozygous loss from single‐copy loss of chromosome 9, a universal event also in very early bladder tumors . To definitively test the accuracy of inferring copy number alterations would require copy‐number data from a similar series of recurrences, which was not possible due to the quality and amount of DNA obtained.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have indicated that homozygous deletions of CDKN2A , a hallmark of advanced Uro tumors, correlate with progression and occur late in development . We did not observe this pattern, possibly due to difficulty to discriminate homozygous loss from single‐copy loss of chromosome 9, a universal event also in very early bladder tumors . To definitively test the accuracy of inferring copy number alterations would require copy‐number data from a similar series of recurrences, which was not possible due to the quality and amount of DNA obtained.…”
Section: Discussionmentioning
confidence: 63%
“…Only one of the cases, a UP, harbored oncogenic FGFR3 or TERT promoter mutations. This tumor, which also had oncogenic PIK3CA , KMT2D , and CDKN1A mutations, had a mutational profile common to that observed in urothelial carcinoma . While morphologic evaluation of this tumor, which consisted of a single small papillary lesion, was compatible with the diagnosis of papilloma, it arose in a patient who had several low‐grade non‐invasive papillary urothelial carcinomas prior and subsequent to the index UP tumor.…”
Section: Resultsmentioning
confidence: 85%
“…We also hypothesise that mutations in DNA repair genes play a larger role than we detected. Mutations in ERCC2 were reported recently in 11 of 32 high-grade Ta samples (Pietzak et al, 2017). We found one missense mutation in ERCC2 , one in ATM , one in FANCD2 and two in FANCM in exome-sequenced samples.…”
Section: Discussionmentioning
confidence: 86%